If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y(y + -3) = 5y + -27 Reorder the terms: 7y(-3 + y) = 5y + -27 (-3 * 7y + y * 7y) = 5y + -27 (-21y + 7y2) = 5y + -27 Reorder the terms: -21y + 7y2 = -27 + 5y Solving -21y + 7y2 = -27 + 5y Solving for variable 'y'. Reorder the terms: 27 + -21y + -5y + 7y2 = -27 + 5y + 27 + -5y Combine like terms: -21y + -5y = -26y 27 + -26y + 7y2 = -27 + 5y + 27 + -5y Reorder the terms: 27 + -26y + 7y2 = -27 + 27 + 5y + -5y Combine like terms: -27 + 27 = 0 27 + -26y + 7y2 = 0 + 5y + -5y 27 + -26y + 7y2 = 5y + -5y Combine like terms: 5y + -5y = 0 27 + -26y + 7y2 = 0 Begin completing the square. Divide all terms by 7 the coefficient of the squared term: Divide each side by '7'. 3.857142857 + -3.714285714y + y2 = 0 Move the constant term to the right: Add '-3.857142857' to each side of the equation. 3.857142857 + -3.714285714y + -3.857142857 + y2 = 0 + -3.857142857 Reorder the terms: 3.857142857 + -3.857142857 + -3.714285714y + y2 = 0 + -3.857142857 Combine like terms: 3.857142857 + -3.857142857 = 0.000000000 0.000000000 + -3.714285714y + y2 = 0 + -3.857142857 -3.714285714y + y2 = 0 + -3.857142857 Combine like terms: 0 + -3.857142857 = -3.857142857 -3.714285714y + y2 = -3.857142857 The y term is -3.714285714y. Take half its coefficient (-1.857142857). Square it (3.448979591) and add it to both sides. Add '3.448979591' to each side of the equation. -3.714285714y + 3.448979591 + y2 = -3.857142857 + 3.448979591 Reorder the terms: 3.448979591 + -3.714285714y + y2 = -3.857142857 + 3.448979591 Combine like terms: -3.857142857 + 3.448979591 = -0.408163266 3.448979591 + -3.714285714y + y2 = -0.408163266 Factor a perfect square on the left side: (y + -1.857142857)(y + -1.857142857) = -0.408163266 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 2y+108=8y | | 28u-10u=175 | | x/7=4/21 | | -5x=-45000 | | -2a+2-5a=-14 | | 4+6=7x-5 | | 125-13x=21x-75 | | f(n)=n | | f(n)=n+3 | | -7(3a-4)+1=-10a-59 | | 4y+7y-9=180 | | 30x^2-3x-6=0 | | 15x-30=720 | | 1=(2)/(x^2)-(x-1)/(x+1) | | 12.5+0.5m=42 | | 4y+6y=y | | 24x^2+48=0 | | 23-x/4=11 | | V=0.125s | | (1-6i)-(5+4i)-(-6+i)= | | 9n+6+9=0 | | .4h-7=2.4-2h+3 | | 2x^2+x+j=0 | | 3x^2-36x+12=0 | | r+.25=.75 | | -(2f-4)=-4(-f+2) | | 3y-1+y+29=6y+30-4y | | -t+5=5-19 | | -3=-6/5*2+b | | ((5x^2)-2x)*((x^2)-x+5)=0 | | 16a^2-81y^2=0 | | -3z+15=6z-13 |